Enhancing Diagnosis Through RNA Sequencing - Murdock, David R (Clinics in laboratory medicine, 2020)
The diagnostic rate of comprehensive genomic sequencing remains only 25% to 30% due to the difficulty in interpreting variants of uncertain significance and noncoding mutations and in elucidating downstream effects of these and other genetic changes. Unlike DNA sequencing, RNA sequencing (RNAseq) reveals the functional consequence of genetic variation through the detection of abnormal gene expression levels, differences in gene splicing, and allele-specific expression. RNAseq can provide nearly 40% improvement in diagnostic rates depending on disease and tissue source. In this burgeoning era of precision medicine, RNAseq offers a powerful tool to improve diagnostic rates and understand disease mechanisms.